'A good quire of voices' : the provision of choral music at St George's Chapel, Windsor Castle, and Eton College, c.1640-1733 /: the provision of choral music at St George's Chapel, Windsor Castle, and Eton College, c.1640-1733. (2019) - Dexter, Keri
No abstract available